Pengelompokkan Data Obat-Obatan Pada Pelayanan Kesehatan Menggunakan Algoritma K-Means Clustering - Saptiani, Anita; Huda, Baenil; Novalia, Elfina; Purba, Arif Budimansyah (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
ABSTRACT In planning accurate drug needs, the drug procurement becomes more effetive and efficient, so that it can be available with the type and amount that is needed. Clustering data mining can be used to analyze drug usage, drug palnning and management at the health center. The method that will be applied is the clustering method on drug data using the K-Means algorithm which can divide data into clusters so that data has similarities will be grouped into one group and different data will be combined in other groups. The purpose of this study was to classify drug data at the Karangsambung health center which could be used as a reference for decision making in planning and supplying drugs at the Karangsambung health center. The results of this study are classifying the level of drugs use at the Karangsambung health center, where the data was taken from 2019 to 2022. The resulting data was grouped into 3 clusters, which later collected high, medium and low usage.